Ethnographic encounters in Israel : poetics and ethics of fieldwork - Markowitz, Fran (Indiana University Press, 2013)
Israel is a place of paradoxes, a small country with a diverse population and complicated social terrain. Studying its culture and social life means confronting a multitude of ethical dilemmas and methodological challenges. The first-person accounts by anthropologists engage contradictions of religion, politics, identity, kinship, racialization, and globalization to reveal fascinating and often vexing dimensions of the Israeli experience. Caught up in pressing existential questions of war and peace, social justice, and national boundaries, the contributors explore the contours of Israeli so.